Membangun model kebijakan melalui analisis psikososial pada penderita HIV/AIDS perempuan di Surabaya - M G Bagus Ani Putra (Masyarakat, Kebudayaan dan Politik, 2016)
This research aims to obtain policy model toward psychosocial analysis to HIV/AIDS women survivors in Surabaya. The model was developed by relation between HIV infection status and psychological condition (religiousness, subjective well being, perception of social support and perception of stress). Data collection technique applied in this research is interview and questionnaire toward 28 HIV/AID women survivors in Surabaya. Subjects were selected from 50 women survivors in Surabaya to gain positive HIV diagnosis. Data analysis method was statistical test with correlation analysis between psychological and medical variable. As the result, there is no correlation between HIV infection status and psychological condition of women survivors in Surabaya. But in a partial analysis, there is a correlation between HIV infection status and religiousness, subjective well being, perception of social support. Some of variables that have partial correlation to be dimensions of model that propose as a basic of policy to treat HIV/AIDS women survivors in Surabaya.